Cell Cycle Protein Expression in Neuroendocrine Tumors: Association of CDK4/CDK6, CCND1, and Phosphorylated Retinoblastoma Protein With Proliferative Index. Issue 10 (November 2017) - Shi, Yan; Qian, Zhi Rong; Zhang, Sui; Li, Wanwan; Masugi, Yohei; Li, Tingting; Chan, Jennifer A.; Yang, Juhong; Da Silva, Annacarolina; Gu, Mancang; Liu, Li; Hamada, Tsuyoshi; et al.
Abstract : Objectives: Dysregulation of the cell cycle has been observed and implicated as an etiologic factor in a range of human malignancies, but remains relatively unstudied in neuroendocrine tumors (NETs). We evaluated expression of key proteins involved in cell cycle regulation in a large cohort of NETs. Methods: We evaluated immunohistochemical expression of CDKN1B, CDKN1A, CDKN2A, CDK2, CDK4, CDK6, cyclin D1, cyclin E1, and phosphorylated retinoblastoma protein (phospho-RB1) in a cohort of 267 patients with NETs. We then explored associations between cell cycle protein expression, mutational status, histologic features, and overall survival. Results: We found that high expression of CDK4, CDK6, CCND1, and phospho-RB1 was associated with higher proliferative index, as defined by MKI67. We additionally observed a trend toward shorter overall survival associated with low expression of CDKN1B. This association seemed strongest in SINETs (multivariate hazards ratio, 2.04; 95% confidence interval, 1.06–3.93; P = 0.03). We found no clear association between CDKN1B mutation and protein expression. Conclusions: Our results suggest that dysregulation and activation of the CDK4/CDK6-CCND1-phospho-RB1 axis is associated with higher proliferative index in NETs. Investigation of the therapeutic potential of CDK4/CDK6 inhibitors in higher grade NETs is warranted. Abstract : Supplemental digital content is available in the text.